Mapping of Groundwater Distribution in the Piru City Area, West Seram Regency - Banyal, Fakri; Riry, Roberth Berthy; Pinoa, Wiclif Sephnath (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
Groundwater has two types: shallow groundwater and deep groundwater. Shallow groundwater originates from rainwater and is located not far from the soil surface, above an impermeable layer. On the other hand, deep groundwater is rainwater that infiltrates more profoundly into the ground through the processes of absorption and filtration by rocks and minerals within the soil. ArcGIS 10.4.1 spatial data processing includes digitization processes to convert data from raster to spatial data. Aquifer configuration analysis using geoelectrical methods (Schlumberger), further clarified using Stiff diagrams, distinguishes aquifer configurations into several rock sections. The aquifer configuration involves the overlying soil layer, clay, sand-gravel as the aquifer, and rock layers with some occurrences of saline aquifers.